2016
DOI: 10.1371/journal.pone.0154793
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Proteins Secreted from the Oryza meyeriana Suspension-Cultured Cells Induced by Xanthomonas oryzae pv. oryzae

Abstract: Oryza meyeriana, a wild species of rice from China, shows high resistance to Xanthomonas oryzae pv. oryzae (Xoo), the cause of rice bacterial blight, one of the most serious rice pathogens. To better understand the resistance mechanism, a proteomic study was conducted to identify changes in the proteins secreted in embryo cell suspension cultures in response to Xoo. After two-dimensional difference gel electrophoresis (2D-DIGE), 72 differentially expressed protein spots corresponding to 34 proteins were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…In general, the fluctuation of major molecules is well corelated with gene expression (Sana et al 2010;Zha and You 2020); however, inconsistencies have also been observed. Peroxidase expression is not associated with the activity between Nipponbare and O. meyeriana (Chen et al 2016). In the study of Zhang, the expression patterns of four out of eight genes were in contrast to the expression pattens of the proteins (Zhang et al 2019).…”
Section: Consistency In Global Studies Of Transcripts and Proteinsmentioning
confidence: 92%
See 1 more Smart Citation
“…In general, the fluctuation of major molecules is well corelated with gene expression (Sana et al 2010;Zha and You 2020); however, inconsistencies have also been observed. Peroxidase expression is not associated with the activity between Nipponbare and O. meyeriana (Chen et al 2016). In the study of Zhang, the expression patterns of four out of eight genes were in contrast to the expression pattens of the proteins (Zhang et al 2019).…”
Section: Consistency In Global Studies Of Transcripts and Proteinsmentioning
confidence: 92%
“…A similar analysis was performed using a suspension of Oryza meyeriana, a wild species that is strongly resistant to Xoo. Upregulation of the signal transduction protein, LysM receptor-like kinase and defense protein, and downregulation of a ROS enzyme (peroxidase) and cell wall modifications (via expansins and pectin acetylesterase) were reported (Chen et al 2016). Besides, phosphosites identification suggested that phosphorylation of TFs, kinases, epigenetic controlling factors, and disease resistant proteins may be functionally relevant to Xoo resistance in IRBB5 (Hou et al 2015).…”
Section: Response Of Rice To Bacteriamentioning
confidence: 99%
“…gov/geo/) in response to bacterial pathogen Xanthomonas oryzae pv. oryzae in Oryza sativa (subspecies japonica 'IR64' , 'IRBB5' , 'IRBB7') represented by GSE33411 data set and ('Y73') variety represented by GSE36093 dataset (Chen et al, 2016). These datasets consist of transcriptome data with three biological replicates (a total of 51 samples).…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, an effort has been made to dissect the rice-bacterial interaction system at 3, 6, 12, and 24 hours after inoculation (hai) in IR24, IRBB5, IRBB7, Y73 hosts based on publicly available data sets (Chen et al, 2016). Infection with Xanthomonas oryzae pv.…”
Section: Introductionmentioning
confidence: 99%
“…However, no hybrid with commercial rice cultivar with elevated resistance to herbivores have been developed so far. O. meyeriana (2 n = 24, GG genome, about 50 cm tall, perennial) is adapted to survive in harsh environments and possesses many useful traits absent in cultivated rice, including high resistance to rice blast and bacterial blight, which has been transferred to cultivated rice ( O. sativa ) (Yan et al, 2004 ; Han et al, 2014 ; He et al, 2015 ; Chen et al, 2016 ; Cheng et al, 2016 ). O. neocaledonica (2 n = 24, GG genome, 60–80 cm tall, perennial), is the latest species described in the genus Oryza (Nayar, 2014 ).…”
mentioning
confidence: 99%